Autumn Hawk reports contributed by Beth Proescholdt, fall 1997 - Proescholdt, Bethet al (1997)
Fall report of a Hawk watch held at Grammar Grove County Wildlife Area from September 17 through November 28, 1997, contributed by Beth Proescholdt. Also included is the count from another site near Coralville. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1997. Epson - sheet feed/flatbed